2019
DOI: 10.3390/ijms20153620
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Application of Silver Nanoparticles (Ag NPs) for the Prevention of Infection in Healthcare Workers

Abstract: Silver is easily available and is known to have microbicidal effect; moreover, it does not impose any adverse effects on the human body. The microbicidal effect is mainly due to silver ions, which have a wide antibacterial spectrum. Furthermore, the development of multidrug-resistant bacteria, as in the case of antibiotics, is less likely. Silver ions bind to halide ions, such as chloride, and precipitate; therefore, when used directly, their microbicidal activity is shortened. To overcome this issue, silver n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
128
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 201 publications
(135 citation statements)
references
References 139 publications
4
128
0
3
Order By: Relevance
“…Daily wound cleaning with HClO solution (pH 6.5) for 12 days decreased the Pseudomonas aeruginosa (P. aeruginosa) bioburden of infected wounds in db/db diabetic mice but wound healing was delayed [18]. Limiting disinfection treatment with both HClO and chitin-nanofiber sheet-immobilized silver nanoparticles (CNFS/Ag NPs) to 3 days [19][20][21] may suppress these negative effects on wound repair [22]. We previously showed that treating P. aeruginosa-infected wounds on hairless rats with BiSCaO suspension (0.2 wt%, pH 12.3) once daily for 3 days and covering the wound with CNFS significantly decreased the P. aeruginosa bioburden and enhanced healing [23].…”
Section: Introductionmentioning
confidence: 99%
“…Daily wound cleaning with HClO solution (pH 6.5) for 12 days decreased the Pseudomonas aeruginosa (P. aeruginosa) bioburden of infected wounds in db/db diabetic mice but wound healing was delayed [18]. Limiting disinfection treatment with both HClO and chitin-nanofiber sheet-immobilized silver nanoparticles (CNFS/Ag NPs) to 3 days [19][20][21] may suppress these negative effects on wound repair [22]. We previously showed that treating P. aeruginosa-infected wounds on hairless rats with BiSCaO suspension (0.2 wt%, pH 12.3) once daily for 3 days and covering the wound with CNFS significantly decreased the P. aeruginosa bioburden and enhanced healing [23].…”
Section: Introductionmentioning
confidence: 99%
“…The antibacterial effects of AgNPs partly depend on their solubility. In the solution, AgNPs will release a high concentration of Ag ions, which can anchor the protein groups on the cell wall of bacteria and cause protein denaturation to form pores, eventually leading to increased permeability of the cell membrane and an imbalance of homeostasis [60]. In addition, studies have reported that AgNPs entering cells may directly damage DNA, RNA, and chromatin [61,62].…”
Section: Metal Nmsmentioning
confidence: 99%
“…Other noble metals have been used successfully for virus diagnosis and detection. Specifically, AgNPs are among the most employed plasmonic nanostructures for biomedical applications [ 135 , 231 , 232 , 233 , 234 ]. The main advantage of AgNPs lies in their higher extinction coefficient when compared to AuNPs.…”
Section: Diagnostics and Biosensors For Covid-19mentioning
confidence: 99%